Navigation through the Literature on Domestic Violence: Discovering the Told and the Untold - Barsha Biswal; Navaneeta Rath; Muhammad Ridwan (Budapest International Research and Critics University, 2021)
Domestic violence is a social ill having a phenomenal rise across communities, cultures, countries. Even after lot many International Conventions, National legislations to arrest its spread, national governments and international agencies have failed to put an end to it. At the same time its dimensions and depth are on rise. Bulk of studies across geographies has been conducted on domestic violence. This has boosted the interest of the authors to navigate into the existing literature on domestic violence. In this article, the researchers have focused on three aspects of domestic from a longitudinal and spatial standpoint. These three aspects are: Definitional issues of domestic violence, Theoretical discourses on domestic violence and Incidences of domestic violence within a time cohort of 1990-2020 along with a review of the policies and conventions. The desk review method has been adopted as a tool for analysis. The authors have noted that some studies are unique; many of them are overlapping in character. But it cannot be said that the existing literature on domestic violence is exhaustive in nature. While the studies reflect many told, still there are many untold areas which need further exploration and explanation.